2008
DOI: 10.1371/journal.pone.0002223
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Tor Signaling Pathway Is Involved in G2/M Transition via Polo-Kinase

Abstract: The target of rapamycin (Tor) protein plays central roles in cell growth. Rapamycin inhibits cell growth and promotes cell cycle arrest at G1 (G0). However, little is known about whether Tor is involved in other stages of the cell division cycle. Here we report that the rapamycin-sensitive Tor complex 1 (TORC1) is involved in G2/M transition in S. cerevisiae. Strains carrying a temperature-sensitive allele of KOG1 (kog1-105) encoding an essential component of TORC1, as well as yeast cell treated with rapamycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 50 publications
10
69
0
Order By: Relevance
“…Using these criteria, we chose four Ser residues (S348, VOL. 30,2010 Tor DIRECTLY CONTROLS THE Atg1 KINASE COMPLEX 1051 S496, S535, and S541) in addition to the identified serines (Fig. 1C).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Using these criteria, we chose four Ser residues (S348, VOL. 30,2010 Tor DIRECTLY CONTROLS THE Atg1 KINASE COMPLEX 1051 S496, S535, and S541) in addition to the identified serines (Fig. 1C).…”
Section: Resultsmentioning
confidence: 95%
“…The yeast strains and plasmids used in this study are listed in Tables 1 and 2, respectively. Standard techniques were used for yeast manipulation (30). The replacement of Ser residues with Ala to generate the ATG13-SA alleles was performed by PCR-mediated mutagenesis using QuikChange (Stratagene, La Jolla, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haploid cells containing kog1 ts as the sole allele were created by transforming kog1⌬/KOG1 diploids with pRS313(kog1-105) (21). After sporulation, haploid kog1⌬ pRS313(kog1-105) transformants were isolated by tetrad dissection using a standard protocol.…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether TORC1 also mediates the effect of nitrogen starvation on Rho1 activity, we employed a temperature-sensitive mutant of KOG1. 39 After inactivation of TORC1 by shifting the mutant cells to the nonpermissive temperature, we found that the Rho1-mediated CWI pathway was no longer responsive to nitrogen starvation, indicating that TORC1 mediates the effect of nitrogen starvation on the pathway.…”
Section: Torc1 Controls Rho1mentioning
confidence: 84%